Conceptualization of the idea of enmity in early greek pluralists and sophists: from the heavenly to the earthly - Туренко, Віталій Едуардович (Київський національний університет імені Тараса Шевченка, 2025)
The article examines the conceptualization of enmity in the works of early Greek pluralists and sophists, emphasizing its philosophical, social, and rhetorical dimensions. It is demonstrated that enmity in the thought of thinkers such as Empedocles, Anaxagoras, Antiphon, Gorgias, and Thrasymachus is not merely an expression of personal hostility but a structural component of cosmological, ethical, and political discourse. Empedocles’ cosmogonic model, in which Strife i.e. Enmity (Νεῖκος) and Love (Φιλία) shape the formation and dissolution of the cosmos, is analyzed in comparison with Anaxagoras’ interpretation of separation and ordering through Nous (νοῦς, Intellect). It is argued that both thinkers reflect the ancient Greek understanding of opposition as a dynamic force governing reality. The study of sophistic texts highlights how enmity was adapted into legal and rhetorical argumentation, particularly in Antiphon’s critique of law as being "hostile to nature" (πολέμια τῇ φύσει) and in Thrasymachus’ reflections on power and inequality. The research reveals that enmity in early Greek thought functioned both as a cosmic principle and a societal phenomenon, forming the foundation for later philosophical and political theories. The philological analysis of key terms such as Νεῖκος, ἐχθρός, πολέμιος, underscores the conceptual fluidity of enmity across different intellectual traditions. Ultimately, the study contributes to the understanding of how ancient thinkers viewed conflict not as an anomaly but as an essential mechanism of order, shaping ethical and political thought from the archaic to the classical periods.

У статті розглядається концептуалізація ворожнечі у творах ранніх грецьких плюралістів і софістів, наголошується на її філософському, соціальному та риторичному вимірах. Показано, що ворожнеча в думках таких мислителів, як Емпедокл, Анаксагор, Антифонт, Горгій і Фрасимах, є не просто вираженням особистої ворожості, а структурним компонентом космологічного, етичного та політичного дискурсу. Космогонічна модель Емпедокла, в якій Ненависть (Νεῖκος) і Любов (Φιλία) формують формування та розчинення космосу, аналізується у порівнянні з тлумаченням Анаксагором поділу та впорядкування через Nous (νοῦς, Інтелект). Стверджується, що обидва мислителі відображають давньогрецьке розуміння опозиції як динамічної сили, що керує реальністю. Дослідження софістичних текстів підкреслює, як ворожнеча була адаптована до юридичної та риторичної аргументації, зокрема, у критиці справедливості Антіфоном як "ворожого явища до природи" (πολέμια τῇ φύσει) і в роздумах Фрасімаха про владу та нерівність. Дослідження показує, що ворожнеча в ранньому грецькому уявленні функціонувала як космічний принцип і як суспільний феномен, формуючи основу для пізніших філософських і політичних теорій. Філологічний аналіз ключових термінів, таких як Νεῖκος, ἐχθρός, πολέμιος, підкреслює концептуальну плинність ворожнечі в різних інтелектуальних традиціях. Зрештою, дослідження сприяє розумінню того, як стародавні мислителі розглядали конфлікт не як аномалію, а як суттєвий механізм порядку, що формує етичну та політичну думку від архаїчного до класичного періодів.
Концептуалізація ідеї ворожнечі у ранньогрецьких плюралістів і софістів: від небесного до земного
Keywords: enmity; early Greek philosophy; ancient Greek literature; sophists; pluralists; political philosophy; classical philology; ворожнеча; ранньогрецька філософія; давньогрецька література; со-фісти; плюралісти; політична філософія; класична філологія